ASTROPOLITICS AND USA-CHINA'S NEW GEOPOLITICAL RIVALRY AREA - Seyedi Asl, Seyedmohammad (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
Space has always been a place for geopolitical competition, and concepts such as astropolitics have even emerged in the scientific world. However, in the last two decades, technological advances have led to an increase in interest in space activities and new global space competition involving many public and private organizations. In addition to political and commercial competition in the world, China and America have expanded the scope of their competition to somewhere outside the world, that is, outer space, and they are trying not to lag behind their competitors in this field. A new round of competition between China and the United States to return to space was formed, which was reminiscent of the space program competition between the United States and the former Soviet Union. The purpose of this research is to analyze the space competition between America and China from the perspective of space geopolitics, using the concept of Astropolitics. Therefore, this study illustrates the role of contemporary geopolitics in today’s space based on the dynamic nature of astropolitics, and assesses the emerging geopolitical competition behind the rise of international interest in space.